2023
DOI: 10.1111/kykl.12335
|View full text |Cite
|
Sign up to set email alerts
|

Trust plays no role in regional U.S. economic development—And five other problems with the trust literature

Abstract: Economists have developed a vast empirical literature on how cultural traits like generalized trust affect economic output. Much of this literature finds a positive causal relationship between measures of generalized trust, as gathered by international surveys, and economic output. However, the trust literature commits five deadly empirical and theoretical sins that undermine many of its findings. From the quality of the survey questions and responses to the paucity of theoretical models used to explain how tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In other words, these definitions indicate that trust can be considered to be reliant on the good will of others, although Mayer et al [52] have identified trust in others to comprise factors such as expertise, integrity, and benevolence. While trust is important, its effects may also be overestimated [53].…”
Section: Trust In Scientistsmentioning
confidence: 99%
“…In other words, these definitions indicate that trust can be considered to be reliant on the good will of others, although Mayer et al [52] have identified trust in others to comprise factors such as expertise, integrity, and benevolence. While trust is important, its effects may also be overestimated [53].…”
Section: Trust In Scientistsmentioning
confidence: 99%